Field Performance of a Modified Chisel Plow - Osma, Tarig O; Zaied, Moayad B; El Naim, Ahmed M (International Journal of Natural Sciences Research, 2014)
Conventional and modified with wide winged tools chisel plow was operated in clayey. Total field time showed no significant difference between two designs in each location at 0.05 level. The conventional plow showed higher speed than modified plow in the first location and second location. Theoretical field capacity recorded by conventional plow was higher than that recorded by modified plow by 0.11ha/h in the first location and by 0.18ha/h in the second location:, respectively. The effective field capacity of conventional plow was higher than that for modified plow by 0.064 ha / h in the first location and by 0.137 ha / h in second location. Field efficiency of conventional plow was lower than that for the modified plow. Fuel consumption rate recorded by conventional plow was higher than the rate recorded by modified plow by 0.10 L / ha in first location. The results showed that the crop yield recorded by the conventional plow was lower than that recorded by modified plow by 47.7 kg / ha in the first location and by 50.1 kg / ha in the second location.